Targeting proteases and proteolytic processing of unusual N-terminal extensions of Plasmodium proteins: parasite peculiarity - Ankita Tehlan; Abhik Saha; Abhik Saha; Suman Kumar Dhar (Frontiers Media S.A., 2023)
More than sesquicentennial years of malarial research, however the unique malarial parasite, Plasmodium still bewilders us with its atypical characteristic features. Elimination strategies, deeper knowledge of the parasite biology and pathways can help combat this global health concern that affects ∼250 million people annually. In this review, we unveil an unusual phenomenon observed in the parasite proteome, N-terminal extensions in proteins and highlight that the proteases that may be involved in their processing events, are potential candidates to target this pathogen. Plasmodium encodes larger proteins as compared to its eukaryotic counterparts with homology regions present in the C-terminus of the protein. In contrast, the function of unusual extensions in the N-terminus remains mostly elusive. This novelty observed in Plasmodium proteins is collated here with a focus on replication proteins. The plausible functions and prevalence of these extensions, despite the reduction in genome size, through the parasite evolution are also mentioned. We hypothesize that these extensions, propagated via the energy consuming cellular processes in the otherwise host-dependent obligate parasite, are beneficial to the parasite in ways that are yet to be explored. Consequently, targeting the proteolytic processing of these proteins and the involved proteases would serve as a new drug development regimen to tackle the emerging resistance in parasites to existing antimalarials.